CORRECTIVE EFFECT OF PHOTOCOMPOSITION ON THE NON-ENZYMATIC GLYCOSYLATION PROCESSES AND STRUCTURAL CHANGES IN THE PANCREAS IN EXPERIMENTAL TYPE 2 DIABETES MELLITUS - Kurylo, Kh.I.; Nebesna, Z.M.; Klishch, I.M.; Volska, A.S. (World of Medicine and Biology, 2019)
In experimental conditions, on the model of type 2 diabetes mellitus in rats, the effect of goat’s rue (Galega officinalis) based phytocomposition on the processes of non-enzymatic glycosylation, as well as on the morphological state of the pancreatic endocrine apparatus was carried out. It was established that the goat’s rue based phytocomposition and its liposomal form Halevit has a pronounced stabilizing effect on the carbohydrate metabolism disorders and morphological condition of the pancreas endocrine apparatus in the conditions of experimental type 2 diabetes mellitus. At the same time, on the basis of micromorphometric analysis, it can be concluded that the expression of the positive effect on the condition of the rat pancreas’ endocrine part in experimental type 2 diabetes mellitus, the new Halevit composition is dominated by a phytochemical based on goat’s rue.
Keywords: pancreas; streptotrozine; type 2 diabetes mellitus; goat’s rue; blueberry; taurine; liposomal form